LIMBAH TULANG HEWAN SEBAGAI BAHAN PENGGANTI TAMBAHAN CAMPURAN BETON - Rully Angraeni Safitri (Prosiding Simposium Nasional Multidisiplin (SinaMu), 2019)
Concrete is material with satisfy compressive strength, malleable, easily produced, rigid, and economical. This research uses alternative materials in process of mixing concrete environmentally friendly. One alternative used are waste animal bones. The use of this animal bone as a alternative coarse aggregate material for the concrete mixture. This is because the amount of animal bone waste in Indonesia is very much and has not been exploited thoroughly. It can suppress natural damage figures due to wild rock abatting. The purpose of this research is, want to increase the quality of concrete with the added material and animal bones, minimizing the waste of animal bones, creating innovations in the development of environmentally friendly. And the benefits that can be gained from this, for upgrade quality concrete, The latest innovations in the utilization of hard and lightweight animal bone waste are assessed to absorb/substitute coarse aggregate use so that it will affect the weight of concrete, With the use of other added materials such as paddy husk ash and red cement whose characterisiticity almost resembles Portland cement, it can absorb the use of Portland cement in concrete and can be a reference or recommendation for Development in Indonesia that is environmentally friendly. This research uses free variables with the red cement waste brick by 30% & 50% of cement usage, paddy husk ash 20%, and animal bones 15%. In this research, the experimental method was making 4 samples of concrete test objects (15x30) that would be tested in heavy and solid tests at the age of 7.14, and 28 days. From the results of this research in obtaining the weight of concrete using the waste of animal bones is lighter than the weight of normal concrete because of the weight of bone type is much lighter than the rough aggregate in general. The addition of bones in the concrete mixture can reach 89% of the achievement target to produce strong press 35MPa. But the use of pozolan cement can’t be used exceeding 30% of its mixing, because stickiness from pozolan cement not entirely the same as ordinary Portland cement.Keywords: Bones, Concrete Mixture